Utero-vaginal prolapse in primigravida: a case report - Ghose, Seetesh; Samal, Sunita; Coumary, Senthil; P, Pallavee; Jenkins, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
26 years, primigravida, with second degree of uterine prolapse attended to the emergency obstetrics outpatient department, in latent phase of labour. After 6 hours of admission, she entered into active phase of labour and membranes ruptured spontaneously. In spite of adequate uterine contractions, antiedema measures cervix did not dilate further. Finally, she delivered after giving Duhrssen’s incision.